Rooting cuttings of Gardenia jasminoides, Duranta repens, and Bougainville glabra with growth retardants - Wan, Chee Keong (Universiti Pertanian Malaysia, 1982)
Effects of Alar, Ancymidol, and Cycocel on the rooting characteristics were studied on cuttings of Gardenia jasminoides, Duranta rep ens, and Bougainville glabra. Alar and Ancymidol produced a greater number ofadventitious roots in gardenia but not in duranta cuttings. The most significant results were obtained with Alar Imd Ancymidol at 2500 ppm and 200 ppm respectively. The roots of Ancymidol-treated gardenia cuttings were observed to be more fibrous and thinner whilst those of bougainville cuttings were larger in size. Cucocel at 2500 ppm seems to have a inhibitory effect on root formation in gardenia cuttings. Root growth and rooting percentage of the three species studied were not affected by the growth retardants.